Penyuluhan Kesehatan Tentang “Mata Sehat, Belajar Semangat: Kenali Dan Atasi Sakit Mata” Di SMK IT Subulussalam Samarinda - Tri Ratnasari; Jihaan Nazhiirah Ilham; Barolym Tri Pamungkas (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Indonesia, as a tropical country, has a high potential for the spread of infectious diseases, including conjunctivitis, or inflammation of the eye membranes. Densely populated residential environments such as Islamic boarding schools and boarding schools are vulnerable to the transmission of this disease due to intense interaction and suboptimal hygiene. Based on various studies, the prevalence of conjunctivitis is quite high among adolescents, especially in boarding-based educational environments. This condition not only disrupts comfort but also impacts the learning and worship processes of students. As a form of promotive and preventive efforts, a health education program themed "Healthy Eyes, Enthusiastic Learning: Recognize and Treat Eye Pain" was conducted at SMK IT Subulussalam Samarinda. This activity aimed to increase students' knowledge about the causes, transmission, and prevention of conjunctivitis, with the hope of encouraging behavioral changes towards a clean and healthy lifestyle. The education was conducted through interactive lectures, discussions, and question-and-answer methods. The results of the activity showed an increase in students' understanding of the importance of maintaining eye and environmental health. It is hoped that this activity can be a real contribution to the pharmacist profession in supporting the creation of a healthy and productive learning environment among adolescents.